2023
DOI: 10.1021/acs.jpcc.2c06048
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbed CO2-Mediated CO2 Photoconversion Cycle into Solar Fuel at the O Vacancy Site of Zirconium Oxide

Abstract: ZrO 2 photoreduces 13 CO 2 under ultraviolet−visible light to 13 C-product(s) negligibly affected by adventitious carbon. The dual-site reaction pathway was theoretically clarified from CO 2 to CO using monoclinic ZrO 2 , followed by multiple hydrogenation steps to methane over Ni nanoparticles. The oxygen vacancy (V O•• ) played essential roles, including the M-shaped CO 2 adsorption over the V O•• site and the direct occupation of the V O •• site by the dissociated O and/or hydroxy group from the hydroxycarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The formation rate was higher using CO 2 and H 2 in the previous paragraph because of the greater light intensity (500 mW cm –2 ) versus that using 13 CO 2 and H 2 (142 mW cm –2 ). The 12 CO ratio in the total CO ( 13 CO and 12 CO) was 30%, significantly higher than the 12 C ratio in the reactant 13 CO 2 (1.0%), suggesting that the reaction intermediate comprising 12 C was concentrated during the photocatalytic test starting from 12 CO 2 adsorbed on surface O vacancy (V O •• ) sites from air. …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The formation rate was higher using CO 2 and H 2 in the previous paragraph because of the greater light intensity (500 mW cm –2 ) versus that using 13 CO 2 and H 2 (142 mW cm –2 ). The 12 CO ratio in the total CO ( 13 CO and 12 CO) was 30%, significantly higher than the 12 C ratio in the reactant 13 CO 2 (1.0%), suggesting that the reaction intermediate comprising 12 C was concentrated during the photocatalytic test starting from 12 CO 2 adsorbed on surface O vacancy (V O •• ) sites from air. …”
Section: Resultsmentioning
confidence: 95%
“…12 CH 4 was likely derived from MXene decomposition and not the photocatalytic product. True intermediate species, e.g., O–C–OH, , was not detected in the FTIR spectrum (Figure a) due to the relatively short lifetime on the photocatalyst surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out in Ref. [43][44][45][46], the most viable route to form CO on ZrO 2 consists of CO 2 adsorption at an oxygen vacancy, a step that is followed by the oxygen transferring to fill the vacant site. Upon formation on ZrO 2 surface, the primary interaction of CO occurs through the carbon atom (see Figure 2 (a)) with Zr 4 + centers, which has a CÀ O stretching mode located at 2129 cm À 1 and ṽcalc = 2167 cm À 1 .…”
Section: Zro 2 (S) Interacting With H 2 and Comentioning
confidence: 99%
“…15,17,18 In particular, V O s not only narrow the bandgap of ZrO 2 but also play a critical role as trap sites for molecules and intermediate compounds. 19,20 The previously reported examples have already demonstrated that the photocatalytic performance can be improved through defect formation. However, the effect of crystal phases, which is one of the factors that most strongly influence photocatalytic reactions and is frequently discussed for nondefective metal-oxide photocatalysts, 21,22 has received less attention for defective ZrO 2−x .…”
Section: Introductionmentioning
confidence: 99%